Synthesis and characterization of Turbinaria ornata mediated Zn/ZnO green nanoparticles as potential antioxidant and anti-diabetic agent of enhanced activity - Diab, Amira S.; Elsayed, Khaled N. M.; El-Sherbeeny, Ahmed M.; Al Zoubi, Wail; Bellucci, Stefano; Abukhadra, Mostafa R. (Frontiers in Marine Science, 2024)
Turbinaria ornata marine macro-algae (TUN) have been applied as carriers for the metallic zinc/ZnO blended nanoparticles, which were synthesized by implementing the extracted phytochemicals of the algae. The resulting hybrid bio-composite (Zn@ZnO/TUN) was characterized as a potential product of promising antioxidant and antidiabetic characteristics in synergetic studies. The obtained composite demonstrate t6he existing or complex biological active groups related to zinc (Zn-O stretching and tetrahedral Zn coordination) and organic groups (amino, methyl, carboxylic, alkynes, P=O, C–C–O, C=N, and N–O) corresponding to the extracted phytochemicals of algae (polysaccharides, phospholipids, lipids, fucose, and phosphodiester). The assessment of Zn@ZnO/TUN hybrid as an anti-oxidant agent validated excellent effectiveness towards the commonly examined radicals (DPPH (88.2 ± 1.44%), nitric oxide (92.7 ± 1.71%), ABTS (90.5 ± 1.8%), and O2●− (30.6 ± 1.32%), considering the determined performance for the commercially used standard (ascorbic acid). Regarding the antidiabetic properties, the incorporation of Zn@ZnO/TUN inhibits the function and activities of the key oxidizing enzymes, either the commercial forms (α-amylase (88.7 ± 1.3%), α-glucosidase (98.4 ± 1.3%), and amyloglucosidase (97.3 ± 1.4%) or the crude intestinal active forms (α-amylase (66.2 ± 1.4%) and α-glucosidase (95.1 ± 1.5%). This inhibitory effectiveness of Zn@ZnO/TUN is significantly better than the measured performances using commercialized miglitol drugs and slightly better than acarbose. Considering the expense and adverse effects of conventional medications, the synthesized Zn@ZnO/TUN blend could be evaluated as a marketable antidiabetic and antioxidant medication. The findings also demonstrate the influence of the derived phytochemicals from Turbinaria ornata and the incorporation of its algae residuals as carriers for the metal nanoparticles on the biological function of the composite. The cytotoxicity investigation reflected safety effect of the composite on colorectal fibroblast cells (CCD-18Co) (96.3% cell viability) and inhibition effect on cancerous colorectal cells (HCT-116) (47.3% cell viability).